Implementasi E-Commerce Pada Toko Jam Dengan CMS (Contens Managemen System ) Wordpress - syarifudin, amir; , Aris Rakhmadi S.T, M.Eng (2016)
The use of technology in developing a business is important to survive in competition every day more hard and tight. One type of use of technology in maintaining and increasing business competition is using electronic commerce (E-Commerce). E-Commerce is a media to promoted a wide range of products and services both in physical and digital form via the Internet. Jamkita store is one of many companies that exist in Indonesia who are trying to survive from the intense competition existing flying businesses. Design ofE-Commercewebsitesjamkita store is using CMS wordpress in the design process. Working sistem of E-Commerce website is illustrated through the use case diagram. Data obtained from the owner jamkita store. The results obtained a E-Commerce website jamkita store that contains information from a wide range of products available in thejamkita store.Website also provides services for users or consumers to order products that are available without having to come directly to the outletjamkita stores.